2017
DOI: 10.1007/978-3-319-39546-3_42
|View full text |Cite
|
Sign up to set email alerts
|

Does Navigation Improve Pedicle Screw Placement Accuracy? Comparison Between Navigated and Non-navigated Percutaneous and Open Fixations

Abstract: Our results confirm the advantages of the navigation technique, which ensures greater accuracy, in open as well as percutaneous procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…In clinical work, there has been a mature binocular technology using the infrared light. Its application in the location and navigation has been spread in clinical medicine and widely used in arthroplasty and pedicle screw placement, such as MAKO and Brainlab . These proactive binocular technologies can be used in navigation and location, whose mechanisms are cumbersome and experience demanding.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical work, there has been a mature binocular technology using the infrared light. Its application in the location and navigation has been spread in clinical medicine and widely used in arthroplasty and pedicle screw placement, such as MAKO and Brainlab . These proactive binocular technologies can be used in navigation and location, whose mechanisms are cumbersome and experience demanding.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the FH technique for screw insertion requires thorough knowledge of anatomical landmarks and pedicle morphology, with accuracy rates reported to be above 90% in most investigations 11,12,14,20) . The use of intraoperative 3-D navigation, on the other hand, has been shown to be superior in terms of radiographic accuracy 7,9,17,22) . In spinal oncology, this technique also offers the advantage of real-time localization and also aids in tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…Pedicle screw insertion can be done using traditional anatomical landmarks via the freehand (FH) technique or with use of intraoperative navigation (NV), among others. Multiple studies have shown improved radiographic accuracy with navigated screws, but the majority of these studies have combined results and included patients with degenerative spine disease, trauma, idiopathic deformity, and to a lesser degree on tumor cases 7,9,17,22) . Although the pedicle screw insertion technique does not vary based on the underlying pathology, the major challenge of placing pedicle screws in patients with metastatic disease is bone quality and potential higher risk for pedicle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…6 Spinal navigation is the best way to ensure greater accuracy of transpedicular screw insertion. 7 Therefore the identification of the vertebral artery course is very important using techniques such as preoperative CTA, preoperative digital subtraction angiography (DSA), and preoperative MR scan or bony computed tomography (CT). After the diagnosis of VAF is confirmed, endovascular embolization is a reasonable treatment option.…”
Section: Discussionmentioning
confidence: 99%